Designing the community training hub pilot as a model for multidisciplinary workforce development - Munoz, Sarah-Anne; Ikiroma, Adalia; Erskine, Rachel; Gray, Trish (Frontiers in Medicine, 2025)
The Community Training Hub (Hub) Pilot aims to contribute towards addressing recruitment and retention challenges in Scotland’s primary care workforce, with a particular applicability to the Remote, Rural and Island (RRI) context. A mixed methods evaluation framework has been designed to assess the effectiveness of the Hub multidisciplinary training across healthcare teams. The pilot involves General Practitioners (GPs), Advanced Nurse Practitioners (ANPs), Pharmacists, and Practice Nurses. This paper outlines the evaluation methodology, focusing on skill development, retention, and collaborative care. The paper argues for further evaluation of the Hub model to assess its potential as a model of distributed training and education to enhance workforce sustainability in rural healthcare.